A Comparative Study of AI-Powered Virtual Assistants in Banking: Features, Benefits, and Challenges - Akinnagbe, Olayiwola Blessing; Akintayo, Taiwo Abdulahi (ALSYSTECH Journal of Education Technology, 2025)
This study examines the adoption of AI-powered virtual assistants in Nigerian banking, focusing on their features, benefits, and challenges. Through a comparative analysis of selected banks, including GTBank, Zenith Bank, and Access Bank, the research highlights key features such as 24/7 customer support, multilingual capabilities, and transaction processing. Benefits include cost reduction, improved customer service, and operational efficiency for banks, as well as convenience and personalized services for customers. However, challenges such as technical issues, low digital literacy, and regulatory compliance hinder widespread adoption. The study concludes with recommendations for stakeholders to enhance the effectiveness of AI-powered virtual assistants, fostering financial inclusion and digital transformation in Nigeria.